Human Surfactant Protein D Suppresses Epithelial-to-Mesenchymal Transition in Pancreatic Cancer Cells by Downregulating TGF-β - Kaur, Anuvinder; Riaz, Muhammad Suleman; Singh, Shiv K.; Kishore, Uday (Frontiers in Immunology, 2018)
Human Surfactant Protein-D (SP-D), an innate immune pattern recognition soluble factor, is known to modulate a range of cytokines and chemokines, such as TNF- and TGF-β at mucosal surfaces during infection, allergy and inflammation. A recent study has shown that treatment with a recombinant fragment of human SP-D (rfhSP-D) for 48 h induces apoptosis in pancreatic cancer cells. Our hypothesis is that at earlier time points, SP-D can also influence key cytokines as a part of its putative role in the immune surveillance against pancreatic cancer, where the inflammatory tumor microenvironment contributes to the epithelial-to-mesenchymal transition (EMT), invasion and metastasis. Here, we provide the first evidence that rfhSP-D can suppress the invasive-mesenchymal properties of highly aggressive pancreatic cancer cells. Mechanistically, rfhSP-D inhibited TGF-β expression in a range of pancreatic cancer cell lines, Panc-1, MiaPaCa-2 and Capan-2, thereby reducing their invasive potential. Smad2/3 expression diminished in the cytoplasm of rfhSP-D treated cells as compared to the untreated control, suggesting that an interrupted signal transduction negatively affected the transcription of key mesenchymal genes. Thus, expressions of Vimentin, Zeb1 and Snail were found to be downregulated upon rfhSP-D treatment in the pancreatic cancer cell lines. Furthermore, blocking TGF-β with neutralizing antibody showed similar downregulation of mesenchymal markers as seen with rfhSP-D treatment. This study highlights yet another novel innate immune surveillance role of SP-D where it interferes with EMT induction by attenuating TGF-β pathway in pancreatic cancer.